2017
DOI: 10.4306/pi.2017.14.2.198
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Self-Report and Measured Smartphone Usage of College Students: A Pilot Study

Abstract: ObjectiveNowadays smartphone overuse has become a social and medical concern. For the diagnosis and treatment, clinicians use the self-report information, but the report data often does not match actual usage pattern. The paper examines the similarity and variance in smartphone usage patterns between the measured data and self-reported data.MethodsTogether with the self-reported data, the real usage log data is collected from 35 college students in a metropolitan region of Northeast Asia, using Android smartph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
83
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(94 citation statements)
references
References 14 publications
9
83
2
Order By: Relevance
“…A previous Korean study showed a significant preference for SNS applications in those addicted to smartphones . In this study, SNS application use was greater in the addicted group, whereas use of entertainment applications was preferred in the non‐addicted group . Some studies on gender differences in problematic mobile phone usage patterns showed that females are more likely to be addicted to smartphones, but the results have not been consistent .…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…A previous Korean study showed a significant preference for SNS applications in those addicted to smartphones . In this study, SNS application use was greater in the addicted group, whereas use of entertainment applications was preferred in the non‐addicted group . Some studies on gender differences in problematic mobile phone usage patterns showed that females are more likely to be addicted to smartphones, but the results have not been consistent .…”
Section: Discussioncontrasting
confidence: 75%
“…29 In this study, SNS application use was greater in the addicted group, whereas use of entertainment applications was preferred in the non-addicted group. 30 Some studies on gender differences in problematic mobile phone usage patterns showed that females are more likely to be addicted to smartphones, but the results have not been consistent. [29][30][31][32] This inconsistency is probably due to diverse reasons, including nationality, included variables and measurement of variables used across the studies.…”
Section: Discussionmentioning
confidence: 99%
“…The participants may thus have overestimated or underestimated their actual and problematic use of the mobile phone. Further research capitalizing on both self-report and mobile phone tracking should be undertaken, as the two types of measurement are not necessarily correlated [68].…”
Section: Discussionmentioning
confidence: 99%
“…Use of social media environments, depending on the benefits individuals get from their social relations and interactions, may increase academic performance. However, in the studies in which academic performance and use of smart phone and social media was reviewed, tendency to further focus on addiction was observed (Lee et al., 2017). Further studies are thought to be needed in order to understand the relation between the use of social media environments and academic performance.…”
Section: Conceptual Frameworkmentioning
confidence: 99%